THE IMPACT OF COMBINED STRESS FACTORS ON THE PROGRESSION OF TYPE 1 DIABETES IN CHILDREN WITH THE EMERGING PREDICTORS OF ITS COMPLICATIONS - OdaіskyiOleksandr; Mityuryayeva, Inga (Eastern Ukrainian Medical Journal, 2025)
Introduction. Type 1 diabetes mellitus (T1DM) and its complications remain one of the leading causes of severe morbidity and disability worldwide, starting from early childhood, and represent one of the most important medical and social problems. According to the International Diabetes Federation, in 2024 more than 9.5 million people worldwide were living with T1DM, including 1.9 million children and adolescents under the age of 20. In Ukraine, over the last two decades before the war, there was a significant increase in the prevalence and incidence of T1DM among children (including during the COVID-19 pandemic). The highest growth rates were observed in the youngest age group (0–6 years), significantly increasing the risk of ischemic heart disease, acute myocardial infarction, chronic kidney disease, neurogenic and vascular disorders, and other diseases later in life. Materials and Methods. The aim of this systematic review was to study current approaches to improving early diagnostic methods for the most common complications of T1DM in children, based on assessing the influence of a complex of psycho-biological stress factors that contribute to the progression of disease severity and the development of target organ damage. A review and analysis of scientific research conducted worldwide and in Ukraine from 2006 to 2024 was performed. Results. The importance of considering stress-provoking risk factors in children was established, including oxidative stress, chronic psychosocial stress, adolescent obesity, imbalances in puberty development, and immune responses against the background of viral and inflammatory processes (including COVID-19). These factors contribute to the activation of progression predictors such as hyperglycemia, dyslipidemia, arterial hypertension, angiopathy, and vascular dysfunctions, leading to the development of diabetic nephropathy, retinopathy, cardiomyopathy, neuropathy, and other complications. The evaluation of potential biomarkers, such as serum cystatin C, urinary cyclophilin A, urinary pentosidine, and neuron-specific enolase, may contribute to preventive diagnostics and risk stratification for damage to the kidneys, eyes, cardiovascular system, nervous system, and other target organs. Conclusions. The predictors of complications in T1DM include both modifiable factors (psychosocial stress, obesity, infectious diseases such as COVID-19, hyperglycemia, arterial hypertension) and non-modifiable factors (age at disease onset, genetic predisposition, disease duration). The use of modern biomarkers in clinical practice improves the efficiency of early detection of subclinical forms of complications and helps optimize individualized prevention strategies. Particular attention should be paid to the early detection of psychosocial stress as an independent risk factor for worsening the course of T1DM. These measures will help implement effective strategies for early diagnosis, monitoring, and prognosis algorithms aimed at reducing disability and mortality rates among children and adults with T1DM in Ukraine, especially considering the strong socio-biological stress factors experienced over the past five years.